IMPACT ON A PERSON’S PROFESSIONAL SPECIALIZATION LATER IN LIFE - Priyadarshini, Dibya (International Journal of Multidisciplinary Research and Studies, 2020)
The family unit is the most fundamental and important structural element of society, and it plays an important role, not only in the life of the person but also in the lives of others around them. There is no way to discount the importance of the nuclear family unit as a social institution in the world we live in today. Even while society and other children at school have an effect on children, the children's families are the primary source of influence in their lives. Both the degree to which the family has an influence on the child and the degree to which the child participates in the family's creative, cultural, social, and moral growth are extremely important aspects to consider. The strength and consistency of the relationship that exists between a kid and his or her parents is one factor that has a role in the child's overall health, including both their mental and physical well-being. According to the findings of a number of studies, the interaction that occurs between children and their parents, as well as the manner in which parents communicate with their offspring, is regarded as the single most important and fundamental factor among the plethora of factors that influence the development of a positive and healthy character in children. This is the case despite the fact that there is a multitude of other factors that influence the development of a positive and healthy character in children (1).